Management of extra hepatic biliary obstruction, in a rural tertiary care hospital India - Joshi, Divyanshu; Monga, Y. P.; Mishra, Shashank; Bansal, Rani; Agrawal, Sachin (International Surgery Journal, 2021)
Background: Extra hepatic biliary obstruction (EHBO) is not a rare surgical problem; our experience in managing 36 patients over a period of two years at a tertiary care hospital in a rural setting in India. The objective was to study the etiology and clinical presentation of patients with EHBO, role of various investigative modalities and management strategies in these patients and their outcome. Methods: This was a prospective study conducted between September 2018 to August 2020 in the department of surgery in tertiary care center Subharti medical college (SMC) Meerut. Data was taken in a pre-formed performa and the results were tabulated and analyzed (descriptive analysis). Results: Out of 36 patients, 2 (5.5%) patients underwent choledochoduodenostomy, 1 (2.7%) exploratory laparotomy with CBD exploration with t tube drainage, 1 (2.7%) ERCP with pigtail drainage; 17(47.2%) ERCP (endoscopic retrograde cholangiopancreatography) followed by cholecystectomy, 1 (2.7%) open cholecystectomy with t tube drainage, 4 (11.1%) ERCP alone, 2 (5.5%) hepaticojejunostomy, 1 (2.7%) ERCP followed by diverticulectomy, 2 (5.5%) PTBD (percutaneous transhepatic biliary drainage) followed by a triple bypass surgery, 2 (5.5%) PTBD, 1 (2.7%) pylorus preserving pancreaticoduodenectomy, 1 (2.7%) ERCP with sphincterotomy, 1 (2.7%) PTBD followed by whipples procedure. Patients were followed up and 5 (13.8%) patients had recurrence of the disease. Conclusions: EHBO is a hepatobiliary surgical condition caused by both neoplastic and non-neoplastic etiology. Benign pathologies common in younger patients whereas neoplastic conditions in older age. Ultrasonography is the most common investigative modality followed by ERCP with PTBD/ENBD playing an important role in decompression of biliary obstruction as a palliative measure in advanced malignancies.